Chloroplast 16S rRNA sequences from different Triticum species - Rudnóy, Szabolcs (Acta Biologica Szegediensis, 2002)
The wheats (Triticum spp.) form a polyploid series with diploid, tetraploid and hexaploid forms. The wild allotetraploid emmer wheat T. turgidum ssp. dicoccoides (AABB) arose by amphyploidy between the wild diploid wheat T. urartu (AA) and a diploid member of the Aegilops genus (BB). The origin of B genome is still a matter of debate. Hexaploid wheats (AABBDD) may have evolved by hybridisation between the AABB tetraploid as cytoplasm donor and the D genome diploid Ae. taushii. The source of the genomes in hexaploid wheats has been thoroughly investigated. Small subunit rRNAs are widely used for the evaluation of genetic diversity or relatedness between different species. In this work small subunit 16S rDNA sequences from chloroplasts of hexaploid T. aestivum possible ancestors were examined. Sequences of 16S rDNAs in the plastids of Ae. taushii (DD), Ae. speltoides (BB) and T. dicoccum (AABB) were determined. They share complete identity in their 16S rDNA sequence and differ from 16S rDNA of T. aestivum by a single position of the gene.